Reaction softening by dissolution–precipitation creep in a retrograde greenschist facies ductile shear zone, New Hampshire, USA. (25th October 2016) - McAleer, R. J.; Bish, D. L.; Kunk, M. J.; Sicard, K. R.; Valley, P. M.; Walsh, G. J.; Wathen, B. A.; Wintsch, R. P.
Abstract: We describe strain localization by a mixed process of reaction and microstructural softening in a lower greenschist facies ductile fault zone that transposes and replaces middle to upper amphibolite facies fabrics and mineral assemblages in the host schist of the Littleton Formation near Claremont, New Hampshire. Here, Na‐poor muscovite and chlorite progressively replace first staurolite, then garnet, and finally biotite porphyroblasts as the core of the fault zone is approached. Across the transect, higher grade fabric‐forming Na‐rich muscovite is also progressively replaced by fabric‐forming Na‐poor muscovite. The mineralogy of the new phyllonitic fault‐rock produced is dominated by Na‐poor muscovite and chlorite together with late albite porphyroblasts. The replacement of the amphibolite facies porphyroblasts by muscovite and chlorite is pseudomorphic in some samples and shows that the chemical metastability of the porphyroblasts is sufficient to drive replacement. In contrast, element mapping shows that fabric‐forming Na‐rich muscovite is selectively replaced at high‐strain microstructural sites, indicating that strain energy played an important role in activating the dissolution of the compositionally metastable muscovite. The replacement of strong, high‐grade porphyroblasts by weaker Na‐poor muscovite and chlorite constitutes reaction softening. The crystallization of parallel and contiguous mica in the retrograde foliation at the expense of the earlier and locally crenulated Na‐rich muscovite‐defined foliation destroys not only the metastable high‐grade mineralogy, but also its stronger geometry. This process constitutes both reaction and microstructural softening. The deformation mechanism here was thus one of dissolution–precipitation creep, activated at considerably lower stresses than might be predicted in quartzofeldspathic rocks at the same lower greenschist facies conditions.